SOCIAL AND PSYCHOLOGICAL DIMENSIONS OF INTERNET USE EXPERIENCED BY MARITIME STUDENTS - Arceňo, Rose A. (PEOPLE: International Journal of Social Sciences, 2017)
The experiences of students on the Internet were explored in this descriptive research study using the virtual theory as an interpretive lens.of (Rheingold, 2012). This research utilized the Internet Addiction Test (IAT) developed by Dr. Kimberly S. Young (netaddiction.com/internet-addiction-test/). The questionnaires were answered by 707 maritime students, who were enrolled during the first semester of the school year 2010 – 2011 in the Department of Marine Transportation and Marine Engineering of the Palompon Institute of Technology, Palompon, Leyte, Philippines. The researcher modified the responses description. Instead of using mild, moderate and severe levels, she preferred to use always, often, frequently, occasionally, and rarely with the equivalent range of mean values. The respondents felt socially accepted online. The research result revealed that social and psychological dimensions affected the respondents occasionally. This showed that the maritime students did not indulge so much on the Internet. Implications to this are their heavy study load and their high level of concentration in their studies for them to land a job in the companies primarily owned by the Royal Association of Shipowners of Netherlands (KVNR) and some cooperating companies. Conclusively, it provides relevant information on the use of the Internet. The IAT items were categorized by the researcher as social and psychological dimensions. Since the frequency of exposure was looked into in this study, the levels were classified based on how frequent they were engaged in the identified statements.